Quantifying Physical Properties of Three Sphagnum‐Based Growing Media as Affected by Drying–Wetting Cycles - Turunen, M. (2020)
The imaged porosities of the materials differed significantly with decomposition degree. Drying curve observations showed that drying of the materials occurred in three phases with (i) large changes in the air‐filled porosity in the matric potential range 0.2 to 3.2 kPa, (ii) clearly smaller changes at 3.2 to 312 kPa, and (iii) large changes at 312 to 1585 kPa, comparable to the change in the wet end of the drying curves (0.2–3.2 kPa). The aeration of the materials was sufficient for plant growth in the second and third phases, where the amount of easily available water was low. This challenges the suitability of the materials under conditions without regular irrigation. The 3D imaging also revealed how pore‐size distributions shifted toward smaller pore‐size classes with increasing decomposition degree and stress impact of the drying–wetting cycles. However, unexpectedly most of the imaged porosity (≥97%) and height (96–98%) of the samples was recovered during rewetting. Overall, the results demonstrate how the water retention, aeration, and shrinkage properties of growing media are inherently interlinked.